PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Dunggio, Maryam; Putri, Nabila Az-Zahra (Kinerja, 2024)
The purpose of this study is to analyze the influence of training and work motivation on employee performance at PT Waskita Beton Precast Tbk. The research population is employees of the engineering division staff of PT. Waskita Beton Precast Tbk which totals 35 people. The entire population was used as a sample using a saturated sampling technique. The analysis method used is multiple linear regression analysis and for hypothesis testing using t-test. The results of data analysis using regression analysis showed that employee performance was influenced by training and work motivation. The training coefficient was 0.325 and the work motivation coefficient was 0.633. Thus, it can be said that work motivation has a greater influence on employee performance than job training. In addition, the results of this study show that training and work motivation contribute to changes in employee performance by 85.7% while the remaining 14.3% are influenced by other factors that are not analyzed in this study. Meanwhile, the results of hypothesis testing show that training has a positive and significant effect on employee performance and work motivation has a positive and significant effect on employee performance.